Personal music experience : uMusic II - Chew, Mervyn Yip Chun. (2011)
Web 3.0 is believed to be more intelligent and information recommendation will be as big as search in tackling information explosion. This project aims to apply recommendation to music and delivers a hassle-free personalized music system with automatic music selection and maintenance of the smart playlists according to user's music preference. It also focuses on cloud music technology to achieve low setup cost, consumer paying less and music video content.